2019
DOI: 10.1128/msystems.00257-19
|View full text |Cite
|
Sign up to set email alerts
|

Multi-omics Signature of Candida auris , an Emerging and Multidrug-Resistant Pathogen

Abstract: Candida auris is a recently described pathogenic fungus that is causing invasive outbreaks on all continents. The fungus is of high concern given the numbers of multidrug-resistant strains that have been isolated in distinct sites across the globe. The fact that its diagnosis is still problematic suggests that the spreading of the pathogen remains underestimated. Notably, the molecular mechanisms of virulence and antifungal resistance employed by this new species are largely unknown. In the present work, we co… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
83
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 70 publications
(92 citation statements)
references
References 61 publications
7
83
1
1
Order By: Relevance
“…Gluconeogenic genes are also induced in vivo (21,57), and these transcriptional changes are often advantageous for microbial pathogens. Stress resistance induced in the presence of alternative carbon sources has been observed in other Candida species, including C. glabrata and the emerging pathogen C. auris (58,59), and numerous examples of beneficial effects of utilization of alternative carbon sources have been seen in bacterial pathogens. For example, Staphylococcus aureus, a facultative intracellular pathogen, alters its central carbon metabolism to promote its survival in the phagosome (60,61).…”
Section: Discussionmentioning
confidence: 99%
“…Gluconeogenic genes are also induced in vivo (21,57), and these transcriptional changes are often advantageous for microbial pathogens. Stress resistance induced in the presence of alternative carbon sources has been observed in other Candida species, including C. glabrata and the emerging pathogen C. auris (58,59), and numerous examples of beneficial effects of utilization of alternative carbon sources have been seen in bacterial pathogens. For example, Staphylococcus aureus, a facultative intracellular pathogen, alters its central carbon metabolism to promote its survival in the phagosome (60,61).…”
Section: Discussionmentioning
confidence: 99%
“…S639P in FKS1 was recently shown to be the most widespread mutation associated with echinocandin resistance (Chow et al, 2020). A recent multi-omics analysis revealed that although the cell wall remodeling enzymes concentration was lower in C. auris when compared to C. albicans, in a drug-resistant C. auris isolate (MIC fluconazole: > 256 µg/mL, MIC caspofungin: 2 µg/mL) cell wall integrity proteins were upregulated, suggesting that the cell wall metabolism can be adjusted in response to drug treatment (Zamith-Miranda et al, 2019).…”
Section: Mechanisms Of Drug Resistance In C Aurismentioning
confidence: 99%
“…C. auris metabolism favors respiration as evidenced by enrichment in glycolytic and sugar transporter gene expression during yeast growth (Yue et al, 2018) and TCA cycle protein enrichment compared to C. albicans (Zamith-Miranda et al, 2019). Respiratory metabolism enhances ATP production and can reduce oxidative stress in C. albicans, thus promoting in vivo fitness and fluconazole resistance (Guo et al, 2017).…”
Section: Stress Resistance and Persistencementioning
confidence: 99%
See 1 more Smart Citation
“…Here, a number of important transcripts were differentially expressed, particularly adhesins IFF4 and CSA1, ALS-gene family members, and other biofilm related genes, such as secreted aspartyl protease and extra-cellular matrix related components. More recently, it has been reported through the use of multi-omics approaches that in comparison to C. albicans, C. auris exhibits significant differences in carbon utilisation and downstream cellular protein and lipid content [32]. It is likely that further pathogenic insights will begin to emerge as large scale data-sets are produced.…”
Section: Is Candida Auris a Virulent Pathogen?mentioning
confidence: 99%